Molecular dynamics studies of hydrogen diffusion in tungsten at elevated temperature: Concentration dependence and defect effects. (1st January 2020) - Wang, Li-Fang; Shu, Xiaolin; Lin, De-Ye; Lu, Guang-Hong; Song, Hai-Feng
Abstract: Influence of hydrogen concentration and defects introduced by neutron irradiation on hydrogen diffusion in tungsten has been investigated by molecular dynamics simulation at elevated temperatures. Hydrogen diffusion is shown to be significantly restrained at high concentrations due to spontaneous formation of platelet-like hydrogen clusters. For neutron irradiation defects, self-interstitials, mono-vacancies and vacancy clusters are considered. By clustering and acting as dislocation loops, self-interstitials show considerable trapping effects on hydrogen, leading to the suppression of hydrogen effective diffusion and the change of diffusion model in which hydrogen mainly diffuses along dislocation lines instead of hopping between tetrahedral interstitial sites. Moreover, an equation connecting hydrogen diffusion parameters and the total length of dislocation loops is empirically established. Different influences of mono-vacancies and vacancy clusters on hydrogen diffusion have been carefully identified. With the same vacancy concentration, hydrogen diffusivity is lower with mono-vacancies than that with vacancy clusters because more isolated trapping sites are provided by mono-vacancies. This work is not only helpful for understanding the synergistic effects of neutron irradiation and plasma interaction, but also potentially applicable for larger scale simulations as input data. Highlights: H diffusion is restrained at high concentration due to spontaneous cluster formation. Self-interstitials show trapping effects on H by forming dislocation loops. H is found to diffuse along dislocation lines, leading the suppression of mobility. Different influences of isolated and clustered vacancies on H diffusion is identified.